Fewpal
+1 vote
532 views
in Mathematics by (127k points)

Prove that cos(3π/2+x)cos(2π+x) [cot(3π/2-x) + cot(2π + x)] = 1

1 Answer

+2 votes
by (64.2k points)
selected by
 
Best answer

Using the sum of angles identities: 
cos(3π/2+x) = cos(3π/2)cos(x) - sin(3π/2)sin(x) = sin(x) 
cos(2π+x) = cos(x) 
cot(3π/2-x) = [cot(3π/2)cot(x) + 1]/[cot(x) - cot(3π/2) = 1/cot(x) = tan(x) 
cot(2π+x) = cot(x) 

Substituting into the original equation: 
cos(3π/2+x)cos(2π+x) [cot(3π/2-x) + cot(2π + x)] = 1
sin(x)cos(x)[tan(x)+cot(x)] = 1 
sin(x)cos(x)[sin(x)/cos(x) + cos(x)/sin(x)] = 1 
sin²x + cos²x = 1

Welcome to Sarthaks eConnect: A unique platform where students can interact with teachers/experts/students to get solutions to their queries. Students (upto class 10+2) preparing for All Government Exams, CBSE Board Exam, ICSE Board Exam, State Board Exam, JEE (Mains+Advance) and NEET can ask questions from any subject and get quick answers by subject teachers/ experts/mentors/students.

Categories

...